Detection of fragment migration into the biceps tendon sheath originating from a humeral osteochondrosis lesion – A case report and review of the literature - Brandstetter, Viktoria; Wunderlin, Nadja; Günther, Charlotte (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
The purpose of this report is to demonstrate that radiographic evaluation of the canine shoulder joint alone is not sensitive enough to detect migrated osteochondral fragments within the biceps tendon sheath, as a sequela to osteochondrosis dissecans of the caudal humeral head. A 6-months-old, male, 35 kg Hovawart was referred due to chronic intermittent lameness on the left forelimb. Survey radiographs revealed a semilunar radiolucency surrounded by a moderately sclerotic rim at the caudal aspect of the left humeral head, referred to as osteochondrosis dissecans. However, only computed tomography combined with ultrasonography could clearly confirm a dislodged osteochondral fragment within the left biceps tendon sheath and a consequent tenosynovitis. Arthroscopic treatment on the clinically affected left forelimb followed by an additional approach over the left biceps tendon sheath to remove the migrated fragment resulted in a complete remission of the lameness until the last follow-up one year after surgery. In our opinion, computed tomography should be applied in the medical work up of canine shoulder osteochondrosis (OC) as standard. Combined with ultrasonography, it can further aid in complete evaluation of the shoulder joint and reliable exclusion of displaced osteochondral fragments, which might also be missed during arthroscopy when located too far distally.Ziel dieses Fallberichts ist es, zu zeigen, dass die Röntgenuntersuchung des Schultergelenks allein nicht sensitiv genug ist, um dislozierte Fragmente in die Bizepssehnenscheide als Folge einer Osteochondrosis dissecans (OCD) Läsion am kaudalen Humeruskopf bei Hunden zu diagnostizieren. Ein 6 Monate alter, 35 kg schwerer, männlicher Hovawart wurde aufgrund einer chronisch intermittierenden Lahmheit an der linken Vordergliedmaße überwiesen. Auf den Röntgenaufnahmen zeigte sich eine semilunare Radioluzenz mit sklerotischem Randsaum am linken kaudalen Humeruskopf, typisch für eine osteochondrale Läsion. Jedoch konnte nur durch die Kombination von Computertomografie und Sonografie ein disloziertes osteochondrales Fragment in der linken Bizepssehnenscheide und die daraus resultierende Tenosynovitis eindeutig bestätigt werden. Eine chirurgische Versorgung mittels Arthroskopie, gefolgt von einem Zugang über der linken Bizepssehnenscheide zur Entfernung des migrierten Fragments, führte zu einer vollständigen Remission der Lahmheit bis zur letzten Nachuntersuchung ein Jahr postoperativ. Unserer Meinung nach sollte die Computertomografie als Standard in der Abklärung einer OCD des Schultergelenks bei Hunden eingesetzt werden. In Kombination mit einer Sonografie kann sie zur vollständigen Beurteilung des Schultergelenks und zum zuverlässigen Ausschluss dislozierter osteochondraler Fragmente beitragen, welche auch in der Arthroskopie übersehen werden können.
Keywords: Dog; joint mice; biceps tendinopathy; computed tomography; ultrasonography; shoulder joint